Applying Virtue to Ethics. - Annas, Julia (Journal of Applied Philosophy, 2015)
Virtue ethics is sometimes taken to be incapable of providing guidance for an individual's actions, as some other ethical theories do. I show how virtue ethics does provide guidance for action, and also meet the objection that, while it may account for what we ought to do, it cannot account for the force of duty and obligation.